IDENTIFIKASI BAKAT OLAHRAGA DENGAN MENGGUNAKAN METODE SPORT SEARCH PADA SISWA PUTRA KELAS V SDN 3 MANGARAN KABUPATEN SITUBONDO - Heldie Bramantha (CERMIN: Jurnal Penelitian, 2018)
This research to determine: Sports talent on students of Grade V SDN 3 Mangaran, and know the potential of sports talents of the students of grade V SDN 3 Mangaran Situbondo Regency. The research method used is descriptive. This research would like to describe the gifts of grade V students of State Elementary School 3 Mangaran Situbondo Regency. Population and sample in this research is entire student of class V SDN 3 Mangaran Situbondo Regency amounting 26 people. The test used in this study is 10 items of sports search test by M Furqon H ( 2006: 38). Data analysis techniques using the modification sport search from M Furqon H. Results of this research and analysis is: The level of sporting activity of grade V students of State Primary School 3 in 2016 from the total of 26 students, 10 students (38.5%) gifted sports, and 16 students (61.5%) less talented / not talented sport. The potential level of sporting talents of grade V students of State Primary School 3 in 2016 from 26 students, 4 students (15.4%) potential as prospective athletes, 6 students (23%) are quite potential as prospective athletes, 11 students (42.3%) were less potential as prospective athletes and 5 students (19.2%) are not potential candidates for athletes.